Rare Earth Elements Geochemistry and Nd Isotopes in the Mississippi River and Gulf of Mexico Mixing Zone - Adebayo, Segun B.; Cui, Minming; Hong, Travis; White, Christopher D.; Martin, Ellen E.; Johannesson, Karen H. (Frontiers in Marine Science, 2018)
Rare earth elements (REE) concentrations were measured in surface waters collected across the salinity gradient in the Mississippi River estuary (i.e., Mississippi River plume, MRP), which includes the near-shore portion of the Louisiana Shelf. In addition, the neodymium (Nd) isotope compositions of two river water samples, and the acid leachable fractions of the associated suspended particulate matter (SPM), were quantified to compare Mississippi River water, and SPM with Gulf of Mexico waters. Despite the spatial limitations associated with sampling due to the size of the Mississippi River system, this study provides some important insights into the REE geochemistry of the MRP. The Mississippi River and its estuarine waters are enriched in the heavy REE (HREE) compared to the light REE (LREE) when normalized to shale composites. All water samples from the estuary also exhibit substantial negative Ce anomalies. In contrast to the majority of other estuaries investigated, removal of REE in the low salinity reaches of the Mississippi River estuary is less substantial. For example, approximately 50% of the river borne Nd is removed in the low salinity region (S < 10) of the Mississippi River estuary compared to the estimated global average of ca. 70% removal of Nd for estuaries worldwide. We propose that the relatively low REE removal in the Mississippi estuary reflects the high pH ( 8) of the Mississippi River, where REE complexation with carbonate ions and natural organic ligands act to stabilize REE in solution. The Nd isotope composition of Mississippi River water near its outflow to the Gulf of Mexico is εNd(0)= -10.5. The acid leachable fraction of the associated SPM is more radiogenic (-9.95 ≤ εNd(0) ≤ -9.77), and closer to the generally more radiogenic Gulf of Mexico (εNd(0) = -9.0). Sequential extraction of the Mississippi River bank sediment reveals substantially different Sm/Nd ratios for the operationally defined fractions of the sediment, which suggests variations in Nd isotope compositions between the labile fractions and the bulk sediment.